ENGINEERING APTITUDE-MECHANICAL REASONING OF ENGINEERING STUDENTS: RASCH ANALYSIS - Firdaus MS; Eddy Saud (UNMUHBABEL Press, 2024)
It is necessary to conduct an analysis with accurate and current modeling regarding engineering aptitude-mechanical Reasoning. Therefore, this study aims to analyze the aptitude-mechanical reasoning technique with Rasch analysis. This study is a quantitative study with a cross-sectional study design. This study was conducted at the Faculty of Engineering, Ogan Komering Ilir Kayuagung Islamic University (UNISKI). The subjects of this study were selected by purposive sampling, so the number of participants in this study was 62 engineering students. The instrument used in this study was an adoption test from MacKellar's book entitled Mechanical, Spatial, Abstract Reasoning. The research data were analyzed using the RASCH Model Analysis using the WINSTEP application. Based on the validity and reliability analysis results, the instrument for measuring engineering aptitude in this study was valid and matched the characteristics of Rasch modelling. The fit/suitability test results with Rasch modelling showed that only 1 participant did not meet two criteria, so they were classified as unfit. The results of the DIF analysis showed that the item that experienced bias with a probability of 0.0002 <0.05 was item number 17; it was seen that the item was straightforward to answer by the mechanical engineering study program, resulting in data bias between the two study programs. The results of the LVP analysis show that the engineering aptitude category is dominated by the moderate category, 73.07% for mechanical engineering study programs and 77.14% for civil engineering study programs.